Investigating a biomarker‐driven approach to target collagen turnover in diabetic heart failure with preserved ejection fraction patients. Effect of torasemide versus furosemide on serum C‐terminal propeptide of procollagen type I (DROP‐PIP trial). (11th September 2017) - Trippel, Tobias Daniel; Van Linthout, Sophie; Westermann, Dirk; Lindhorst, Ruhdja; Sandek, Anja; Ernst, Stefanie; Bobenko, Anna; Kasner, Mario; Spillmann, Frank; González, Arantxa; López, Begoña; Ravassa, Susana; et al.
Abstract : Aim: Heart failure with preserved ejection fraction (HFpEF) is associated with myocardial remodelling including severe pro‐fibrotic changes contributing to an increase in left ventricular stiffness and diastolic dysfunction. Serum C‐terminal propeptide of procollagen type I (PIP) strongly correlates with the turnover of extracellular cardiac matrix proteins and fibrosis. Torasemide, but not furosemide, was described to reduce collagen type I synthesis in clinically unstable patients with heart failure with reduced ejection fraction. We evaluated whether its effect translated to HFpEF patients with type 2 diabetes mellitus (T2DM) and abnormal basal PIP levels. Methods and results: We performed a relatively small, single‐centre, randomised, double‐blind, two‐arm parallel‐group, active controlled clinical trial in 35 HFpEF patients with T2DM to determine the effects of a 9‐month treatment with torasemide vs. furosemide on changes of serum PIP levels. Patients with increased PIP levels (≥110 ng/mL), or evidence of structural changes with a left atrial volume index (LAVI) >29 mL/m 2 and abnormal PIP levels (≥70 ng/mL), were eligible to participate. Fifteen patients were female (42%), mean age was 69 years, body mass index was 34.7 kg/m 2, 83% were in New York Heart Association class II/III. Echocardiographic characteristics showed a mean left ventricular ejection fraction of >60%, a left ventricular mass index >120 g/m 2, an E/e' ratio of 14, and a LAVI of 40 mL/m 2 with a NT‐proBNP of 174 ng/L and a 6‐minute walk distance of 421 m. Mean per cent change in PIP was 2.63 ± 5.68% (±SEM) in torasemide vs. 2.74 ± 6.49% in furosemide ( P = 0.9898) treated patients. Torasemide was not superior to furosemide in improving functional capacity, diastolic function, quality of life, or neuroendocrine activation. Conclusion: In this hypothesis‐generating, mechanistic trial in stable HFpEF patients with T2DM, neither long‐term administration of torasemide nor furosemide was associated with a significant effect on myocardial fibrosis, as assessed by serum PIP. Further studies are urgently needed in this field. More specific diuretic and anti‐fibrotic treatment strategies in T2DM and/or HFpEF are warranted.